STOCK INVESTMENT INTENTIONS AMONG GENERATION Z: THE INTEGRATION OF FINANCIAL LITERACY, TECHNOLOGICAL ACCESS, AND INTRINSIC MOTIVATION - Bintang Triady; Yusnita Octafilia Th. A. Y. I; Yuni Friska; Yolanda Safitri Nelaz (Procuratio : Jurnal Ilmiah Manajemen, 2026)
This study investigates the determinants of stock investment interest in public university students in Pekanbaru City with a focus on the variables of investment knowledge, information technology, minimum capital, and investment motivation. Using a quantitative approach through a survey of 156 respondents and data were analyzed with multiple linear regression. The findings of the study revealed that investment knowledge and investment motivation have a significant and positive influence on investment interest. In contrast, advances in information technology and minimal capital policies have not shown an influence. These results imply the importance of strengthening financial literacy rather than simply digitising platforms for online investment companies to attract young investors. Penelitian ini mengkaji faktor-faktor yang memengaruhi minat investasi saham pada mahasiswa perguruan tinggi negeri di Kota Pekanbaru dengan fokus pada variabel pengetahuan investasi, teknologi informasi, modal minimum, dan motivasi investasi. Penelitian ini menggunakan pendekatan kuantitatif melalui survei terhadap 156 responden, dengan data yang dianalisis menggunakan regresi linier berganda. Hasil penelitian menunjukkan bahwa pengetahuan investasi dan motivasi investasi berpengaruh positif dan signifikan terhadap minat investasi. Sebaliknya, perkembangan teknologi informasi dan kebijakan modal minimum tidak menunjukkan pengaruh yang signifikan. Temuan ini mengindikasikan pentingnya penguatan literasi keuangan dibandingkan sekadar digitalisasi platform bagi perusahaan investasi online dalam menarik minat investor muda.